On One Important Peculiarity of the Imperative Singular in the Dialect of Ararat - Avetyan, Sargis (Bulletin of Yerevan University B: Philology, 2023)
Morphological rules of forming the Imperative in the dialect of Ararat mainly correspond to those applied in the colloquial speech of Literary Modern Eastern Armenian. Nonetheless, some subdialects have an important peculiarity – an ա vowel-final rather than ի vowel-final form in the Imperative singular of transitive simple verbs of the the է (< Old Arm. ե and ի) conjugation - which, to our knowledge, so far has not been explained properly from either a diachronic or synchronic perspective. It is argued that the form in question has been created through analogy with the Imperative singular of three high-frequency transitive verbs (namely, ասել, Imp. sg. ասա՛, ածել, Imp. sg. ածա՛, անել, Imp. sg. արա՛)․ Therefore, it is no accident that only transitive simple verbs of the է conjugation usually show the ending ա in the Imperative singular, whereas intransitive ones in the same conjugation class have regularly preserved the standard ending ի, the latter, in its turn, dating back to the Old Arm. ending իր, or, possibly, the stem-final diphthong եա՛ via the intermediate stage of է (that is, եա՛> է > ի)․ Later the ending ա of the Imperative singular has also been extended analogically from transitive simple verbs of the է conjugation to causative verbs in some subdialects (most regularly in the subdialect of Vaɫaršapat (Ēǰmiacin), where this has become a productive morphological rule that admits of no exceptions).
Keywords: morphological rules, the dialect of Ararat; Imperative singular; transitive simple verbshigh-frequency transitive verbs; the է conjugation,the subdialect of Vaɫaršapat (Ēǰmiacin)